Yam polysaccharide promoted bone differentiation of MC3T3-E1 cells through targeted Inhibition of CASP3 activation - Qiting Yu; LinHui Liu; TaiPing Jiang; Zhiyu Guan; ZhaoMing Liu (Journal of Orthopaedic Surgery and Research)
Abstract Objective Osteoporosis (OP) is a disorder of bone metabolism characterized by decreased bone mass and an increased risk of fractures. Yam polysaccharide (YP) is a natural active component extracted from Dioscorea opposita, which has anti-inflammatory, antioxidant and immunomodulatory effects, but its role and mechanism in bone differentiation remain unclear. The aim of this study was to investigate the protective mechanism of yam polysaccharide in OP. Methods Targets associated with 9 known YP and OP were identiffied from the Swiss Target Prediction, Similarity Ensemble Approach, PharmMapper, and GeneCards databases. A protein-protein interaction (PPI) network was constructed to identify potential therapeutic targets. Concurrently, GO and KEGG analyses were performed to predict potential signaling pathways. Molecular docking studies were performed to predict the binding affinity of YP to targets. An osteogenic differentiation model of MC3T3-E1 cells was used in vitro. The osteogenic potential of the different concentrations (50, 100, 200, and 400 ug/mL) of YP was assessed through CCK-8 cell viability assays, alkaline phosphatase (ALP) staining, Alizarin Red staining, and qPCR. qPCR was used to detect the expression of CASP3, AKT and PI3K mRNA, and WB was used to detect the expression of P-AKT, and P-PI3K proteins. Results The successfully constructed PPI network and molecular docking revealed the CASP3, HMGCR, HSP90AA1and PTGS2 proteins as the core targets, all of which showed good binding activity with YP. GO and KEGG analyses suggested the biological roles of these targets, demonstrating that YP interacts with 81 pathways in OP. Notably, the PPAR signaling pathway was identified as a key pathway mediating YP’s effect on OP. In vitro cell experiments demonstrated that Yam polysaccharides significantly promoted the proliferation of MC3T3-E1 cells across all concentration groups, enhanced ALP activity, increased mineralized nodule area, and upregulated the expression of osteogenic marker genes Dlx5, Osx, and Bglap. Importantly, the effects were most pronounced at a concentration of 200 ug/mL for YP. This was attributed to the regulation of CASP3 expression and the AKT/PI3K signaling pathway. Conclusion This study first predicted the potential targets and pathways of YP through network pharmacology analysis, suggesting that its effect on YP might be achieved through the expression of CASP3 and the AKT/PI3K signaling pathway. These findings indicate that YP is a promising inhibitor for OP driven by excessive activation of CASP3.